Pengaruh Cita Rasa, Harga, Terhadap Kepuasan Konsumen pada Warkop Milenial Rantauprapat - Junita Lubis; Novrihan Leily Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the influence of taste and price on consumer satisfaction in Rantauprapat Millennial Warkop. This type of research is associative research. Data collection in this study was carried out through a survey approach with a type of quantitative descriptive research by distributing questionnaires to 100 respondents, while the population used in this study was millennial warkop customers of Rantauprapat. Data collection techniques are carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study uses SPSS. The data analysis technique in this study is descriptive analysis. The results of this study show that taste and price affect customer satisfaction at Rantauprapat Millennial Warkop.